TINJAUAN INCE DALAM STRUKTUR KEKERABATAN KETURUNAN MELAYU DI KABUPATEN PANGKEP - Rostina . ,; Mubarak dahlan .; Ibrahim . , (ALLIRI Journal of Anthropology, 2022)
ABSTRACT This study aims to determine: 1) the origin of the arrival of the Ince Malay descendants in Pangkep; 2) Ince's kinship system in Pangkep Regency; 3) The existence of Malay culture in the Ince Malay community in Pangkep. This research uses descriptive qualitative research. The research subjects are people who come from Ince Malay descent and members of the Ince/Intje Malay family bond community (IKRM). Then in the process of collecting data used observation techniques, interviews, and documentation. The results showed that: 1) The Ince title was a title given to the Malay nobility in Sulawesi. The beginning of the arrival of these descendants in Pangkep around the 16th century in 1561 which was marked by the arrival of the Chatib including Datuk Ri Bandang, Datuk Ri Tiro, and Datuk Patimang. At the time of his arrival the title Ince was already used as the identity of the Malay descent. They came with two missions, namely spreading Islam and trading. Starting from there, his staff who came from Malay aristocrats married girls in Lempangeng and spread to Parang-parang and Tekolabbua; 2) The kinship system adopted by the Ince Descendant Community is a Unilateral kinship system, namely the kinship system through only one line of relationship, namely through the patrilineal or patrilineal lineage. So who can give the title Ince to his name when his father is of Malay descent. In the kinship system, Ince descendants are free to marry non-Ince descendants. 3) The existence of Malay culture in the Ince Malay descendants has now begun to erode. Apart from the very distinctive name, there is also something that is believed by the Ince community in the form of ideas or ideas in the form of regulations, namely the prohibition of eating small shrimp (Ambari/Balacang).